If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -15) = x Reorder the terms: (-15 + 2x) = x Remove parenthesis around (-15 + 2x) -15 + 2x = x Solving -15 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -15 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x -15 + 1x = x + -1x Combine like terms: x + -1x = 0 -15 + 1x = 0 Add '15' to each side of the equation. -15 + 15 + 1x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 1x = 0 + 15 1x = 0 + 15 Combine like terms: 0 + 15 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| -12a+4(-19+4a)=-56 | | -4a+b=19 | | 154-6x=6x+107 | | -6(6)+y=-33 | | 3x-99=-81 | | -15x+3(-33+6x)=-81 | | 5x+4=-3+3x+19 | | 5x+18=6x+7 | | 3+0,4x=1000/x+3+0.2x | | -8x+2y=-36 | | -5+y=-23 | | (-3x+8)(9x-7)=0 | | (7x-4)(8x+3)=0 | | (4x+1)(5-2x)=0 | | k+6k-9=0 | | 10x+15=25x+45 | | 6x-8+2x+16=80 | | 7x+5y+7x-2x+4z-7y= | | 4x+10=80-3 | | 5x^0=5 | | 5x^0=1 | | 5x^4=2 | | 5x^3=2 | | p^3-p^2-p+1=0 | | 435=(1+n)/2*n | | 2x-9=69-11x | | 20xy+24y=0 | | Twothirdsx-4=10 | | (11/X)+6 | | 22x=14 | | (4x-3)(4x-3)-49=0 | | -10+4(3p+10)=11 |